2016
DOI: 10.1123/jpah.2016-0402
|View full text |Cite
|
Sign up to set email alerts
|

Results From South Korea’s 2016 Report Card on Physical Activity for Children and Youth

Abstract: Background:South Korea’s 2016 Report Card on Physical Activity for Children and Youth is the first assessment of physical activity according to the indicators set by Active Healthy Kids Global Alliance.Methods:National surveys were used as preferred sources of data. This was then supported by peer-reviewed papers and government reports identified by a systematic search of the literature written in English or Korean. A Research Working Group then graded indicators based on the collected evidence.Results:Each in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 17 publications
2
17
0
Order By: Relevance
“…Low levels of PA have been marked among children and adolescents in Asia. For example, one Japanese study using accelerometers found that children spent over 50% of wear-time on SED per day, whereas the percentage of MVPA time was 7.9% [ 14 ], which was similar to one Korean study [ 15 ]. China, the biggest country in Asia, has suffered the burden of young people’s insufficient PA and excessive SED over the past decades [ 16 ], which has aroused the concerns of policy-makers [ 17 , 18 ].…”
Section: Introductionsupporting
confidence: 61%
“…Low levels of PA have been marked among children and adolescents in Asia. For example, one Japanese study using accelerometers found that children spent over 50% of wear-time on SED per day, whereas the percentage of MVPA time was 7.9% [ 14 ], which was similar to one Korean study [ 15 ]. China, the biggest country in Asia, has suffered the burden of young people’s insufficient PA and excessive SED over the past decades [ 16 ], which has aroused the concerns of policy-makers [ 17 , 18 ].…”
Section: Introductionsupporting
confidence: 61%
“…94 Similarly, 2 consecutive Report Cards from South Korea highlighted that the emphasis on important subjects (eg, math, science) for university admission overrides the importance of physical activity in the Korean education system. 95,96 Although the new 2018 Korean national curriculum requires schools to provide mandatory physical education, it is regarded as a minor subject and, with progressing school grades, it is devalued and neglected. 97 Evidence showed that adding more time to academic or curricular subjects by taking time away from physical education programs was found not to enhance academic achievement in the corresponding academic subjects and to be potentially detrimental to health.…”
Section: Schoolmentioning
confidence: 99%
“…This approach attempted to identify the current and most favored measurement approaches for each recognized component of physical literacy, competence, confidence, motivation, and knowledge, but has been criticized for treating them as quite separate, and still providing a disproportional focus on physical and motor competence. Some national ‘Report Cards on Physical Activity in Children and Youth’ have acknowledged physical literacy as an indicator, however, some countries have expressed that data on physical literacy are ‘insufficient’ to provide an overall grade [ 50 , 51 ].…”
Section: Introductionmentioning
confidence: 99%